On local properties of 1-planar graphs with high minimum degree - Hudák, Dávid (Ars mathematica contemporanea, 2011)
A graph is called 1-planar if there exists its drawing in the plane such that each edge contains at most one crossing. We prove that each 1-planar graph of minimum degree 7 contains a pair of adjacent vertices of degree 7 as well as several small graphs whose vertices have small degrees; we also prove the existence of a 4-cycle with relatively small degree vertices in 1-planar graphs of minimum degree at least 6.
Keywords: 1-planar graph; 1-ravninski grafi; graph theory; lahki grafi; light graph; teorija grafov